2022
DOI: 10.3390/lubricants10100271
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement of the Wear Resistance of T15 Laser Clad Coating by the Uniformity of Microstructure

Abstract: The uniformity of microstructure and wear properties exist in the T15 coating for the laser cladding on 42CrMo steel. It can be improved by a post-heat treatment process. Temperature ranges from 1100 to 1240 °C were applied on the cladding layer to investigate the effect of the heat treatment on the wear resistance and hardness gradient. The post-heat treatment can efficiently improve the inhomogeneity of microstructure. The lower wear rate is obtained after the quenching process at 1100 °C, and the wear rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Decreasing the hardness of the coating will make the wear resistance of the coating material tend to be low [35], [67]- [73]. A increase in stand-off distance results in a decrease in hardness value which will make the mass loss and wear rate of the specimen tend to be high [24], [28].…”
Section: Resultsmentioning
confidence: 99%
“…Decreasing the hardness of the coating will make the wear resistance of the coating material tend to be low [35], [67]- [73]. A increase in stand-off distance results in a decrease in hardness value which will make the mass loss and wear rate of the specimen tend to be high [24], [28].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, wear resistance can be further improved by heat treatment of laser-fused cladding. By heat treating the T15 LC coatings on the surface of 42CrMo steel, Zhang et al [63] showed that the inhomogeneity of this coating could be effectively improved. This treatment resulted in a notable increase in the content of martensite and alloy carbide, consequently enhancing the resistance to abrasion.…”
Section: Improving Coatingsmentioning
confidence: 99%